Activation and recruitment of brown adipose tissue as anti-obesity regimens in humans. (March 2015) - Yoneshiro, Takeshi; Saito, Masayuki
Abstract Brown adipose tissue (BAT) is the site of sympathetically activated adaptive thermogenesis during cold exposure and after hyperphagia, thereby controlling whole-body energy expenditure (EE) and body fat. BAT thermogenesis is primarily dependent on the energy-dissipating activity of uncoupling protein 1 (UCP1). There are two types of UCP1-expressing adipocyte, classical brown and beige/brite adipocytes. Recent radionuclide studies have demonstrated the existence of metabolically active BAT composed of mainly beige/brite adipocytes in adult humans. Human BAT is activated by acute cold exposure, being positively correlated to cold-induced increases in EE. The inverse relationship between the BAT activity and body fatness suggests that BAT, because of its energy-dissipating activity, is protective against body fat accumulation. In fact, either repeated cold exposure or daily ingestion of some food ingredients acting on transient receptor potential channels recruited BAT in association with increased EE and decreased body fat. Moreover, possible contribution of BAT to glucose tolerance has been suggested. In addition to the sympathetic nervous system, some endocrine factors also have potential for activation/recruitment of BAT. Thus, BAT is a promising therapeutic target for combating human obesity and related metabolic disorders.